n → ∞ lim r = 1 ∑ n n ln ( n 2 + r 2 ) − 2 ln ( n ) = ln ( 2 ) + 2 π − 2
We are given the value of the limit above. Suppose we consider the limit below
n → ∞ lim n 2 m 1 [ ( n 2 + 1 ) ( n 2 + 2 2 ) ( n 2 + 3 2 ) … ( n 2 + n 2 ) ] n m
If this limit equals to ( a e b − a ) m for constant m and positive integer a , find the value of b .
Clarification: e = L → 0 lim ( 1 + L ) 1 / L .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
.Excellent solution
l n ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ n 2 m ( k = 1 ∏ n ( n 2 + k 2 ) ) m / n ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ = n m l n ⎝ ⎜ ⎜ ⎜ ⎜ ⎛ n 2 k = 1 ∏ n ( n 2 + k 2 ) ⎠ ⎟ ⎟ ⎟ ⎟ ⎞
and b is not a positive integer.
Log in to reply
Yaa b is not a positive integer thats the mistake in question but my answer is correct . check it again..
L = n → ∞ lim n 2 m 1 [ ( n 2 + 1 2 ) ( n 2 + 2 2 ) ( n 2 + 3 2 ) . . . ( n 2 + n 2 ) ] n m = exp ⎝ ⎛ ln ⎝ ⎛ n 2 m 1 [ r = 1 ∏ n ( n 2 + r 2 ) ] n m ⎠ ⎞ ⎠ ⎞ = exp ( n m r = 1 ∑ n ln ( n 2 + r 2 ) − 2 m ln ( n ) ) = exp ( m r = 1 ∑ n n ln ( n 2 + r 2 ) − 2 ln ( n ) ) = exp ( m [ ln ( 2 ) + 2 π − 2 ] ) = ( e ln ( 2 ) + 2 π − 2 ) m = ( 2 e 2 π − 2 ) m Note that exp ( x ) = e x
⟹ b = 2 π ≈ 1 . 5 7
Problem Loading...
Note Loading...
Set Loading...
Let y = n → ∞ lim n 2 m 1 [ ( n 2 + 1 2 ) ( n 2 + 2 2 ) . . . . . ( n 2 + n 2 ) ] m / n
Taking logarithm both sides and take n 2 m inside the big braces, we get
lo g y = n → ∞ lim n m lo g [ ( n 2 n 2 + 1 ) ( n 2 n 2 + 2 2 ) . . . . ( n 2 n 2 + n 2 ) ]
lo g y = n m r = 1 ∑ n lo g ( 1 + n 2 r 2 )
lo g y = m 0 ∫ 1 lo g ( 1 + x 2 ) d x lo g y = m ( π / 2 + lo g 2 − 2 )
y = e lo g 2 e π / 2 − 2 m
y = ( 2 e π / 2 − 2 ) m
a + b = π / 2 − 2 + 2 = π / 2 which is the final answer.